Development Of Ecological Competence of Future Geography Teachers on The Base of Innovative Approaches - Suyunov Samar Samandarovich (Zien Journals, 2024)
The role of geography education in the implementation of responsible tasks such as prevention of environmental pollution, rational and effective use of available natural resources in Uzbekistan is highlighted. There are some proposals for the development of geography education and increasing its prestige.
Keywords: ecological situation; ecosystem; ecological problems